ENERGY EFFICIENCY THROUGH COMBUSTION SYSTEM OPTIMIZATION IN REHEATING FURNACES - Koray Gencoglan,; Osman Gezgin,; Meliha Rigan, (MATTER: International Journal of Science and Technology, 2025)
Reheating processes, which constitute a critical stage in steel industry production, hold significant importance in terms of energy efficiency due to their high energy consumption. In reheating furnaces, by-product gases, natural gas, or fuel oil are typically utilized. The walking beam reheating furnace examined in this study heats billets to the required temperatures— depending on product size and type—through 32 burners positioned in different furnace zones, providing stepwise heating. However, the imbalance in heat transfer within the furnace and the non-uniform distribution of heating rates lead to deviations from the target heating curve, thereby intensifying the scaling problem that causes production losses. The primary aim of this study is to reduce unnecessary natural gas consumption and minimize the carbon footprint by improving the control of the air–fuel mixture inside the furnace through burner optimization and automation systems. As a result of the implemented measures, considering the annual production capacity, a total of 1,950,000 Sm³ of natural gas savings was achieved, corresponding to approximately 3,705–3,900 tons of CO2 equivalent emission reduction. These findings demonstrate a successful large-scale industrial application aimed at enhancing energy efficiency in reheating furnaces while mitigating environmental impacts.